The Influence of Social Media and Product Innovation on Increasing the Income of Culinary MSMEs - Aini Zufria Ardiana; Diva Aprilia; Fina Oktaviani; Melani Rezeki Romadloni; Lutfi Eko Cahyono (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
MSMEs are micro, small and medium business units owned by individuals with simple assets and technology. MSMEs are the largest sector that provides benefits to Indonesia. MSMEs have improved the Indonesian economy by acting as one of the absorbers of labor, contributing to exports and trade. This study aims to measure the impact of the use of social media, product innovation on increasing the income of Seblak MSMEs in Bojonegoro Regency. Data collection uses a quantitative approach. Sampling uses the Simple random sampling technique. Data collection in this study used questionnaires distributed to seblak MSME actors in Bojonegoro Regency. The results of the study showed that social media did not affect the increase in income of Seblak MSMEs in Bojonegoro Regency. Product innovation has an effect on increasing the income of Seblak MSMEs in Bojonegoro Regency.